Association of the Healthy Dietary Index 2020 and its components with chronic respiratory disease among U.S. adults - Zhiyi, Liu; Shuhan, Zhou; Libing, Zhang; Jiaqi, Li; Xin, Ding; Lingxi, Qin; Yuan-Mei, Shi; Hong, Zhang; Jiaqi, Nie; Hui, Li; Sanyou, Fang (Frontiers in Nutrition, 2024)
Chronic respiratory disease is an important public health problem in the United States and globally. Diet, an important part of a healthy lifestyle, is also relevant to chronic respiratory health. We aimed to explore the relationship between overall dietary quality and the risk of chronic respiratory disease (CRD), include chronic bronchitis (CB), emphysema and asthma.A total of 4499 United States adults were extracted from the National Health and Nutrition Examination Survey (NHANES) in 2017-2018. Diet quality was assessed using two-day, 24-hour dietary recall data and quantified as the Healthy Diet Index(HEI)-2020 score. Binary logistic regression models, Restricted cubic splines (RCS) and generalized additive modeling (GAM), the weighted quartile sum (WQS) and qgcom models were used to assess the relationship between HEI-2020 scores and risk of CB, emphysema and asthma.High HEI-2020 scores are associated with low risk of chronic respiratory disease (CB: 0.98,0.97-0.99; emphysema: 0.98,0.97-0.99; asthma: 0.98,0.97-0.99) and consistent results across different dietary variable categorization (Tertile: CB: 0.58,0.42-0.81; asthma: 0.51,0.35-0.74;Quartile:CB: 0.57,0.34-0.97; asthma: 0.56,0.36-0.86) and different weighting models. Negative dose-response relationship between dietary quality and risk of chronic respiratory disease also shown in RCS and GAM models. The WQS and qgcom models also showed a healthy mixing effect of dietary components on respiratory disease, with high-quality proteins, vegetables, and fruits making the heaviest contributionsHigher HEI-2020 scores were associated with lower risk of CB, emphysema, and asthma. Following Dietary Guidelines for Americans 2020-2025 could support enhanced respiratory health.This study used the NHANES data to explore the relationship between HEI-2020 and the risk of CRD. Given the importance of diet to life and the high prevalence of respiratory diseases represented by asthma, chronic bronchitis, and emphysema in the U.S. population, this study has strong public health implications.